Larangan Jual Beli Pakaian Bekas Impor (Thrift) dalam Regulasi Perdagangan: Perspektif Hukum Islam pada Praktik Perdagangan di Pasar Tugu Pahlawan Pagi Surabaya - Muhammad Gasa Pratama; Lukman Santoso (Jurnal Antologi Hukum, 2025)
The phenomenon of trading imported second-hand clothing (thrift) has become increasingly popular among various segments of society, despite being prohibited under Law Number 7 of 2014 on Trade and Regulation of the Minister of Trade Number 20 of 2022. In practice, such activities remain prevalent at the Tugu Pahlawan Morning Market in Surabaya. This study aims to analyze the practice of trading imported second-hand clothing based on the concept of maslahah and to examine the implementation of trade regulations concerning this prohibition. This research employs a qualitative method with an empirical approach, utilizing observation, interviews, and documentation for data collection. The findings indicate that the practice of trading imported second-hand clothing provides benefits for both sellers and buyers and fulfills elements of maslahah in terms of dharuriyah, hajiyah, and tahsiniyah. However, when viewed from the perspective of maslahah ‘ammah, the government’s prohibition seeks to realize broader public welfare and therefore should be prioritized. Furthermore, the implementation of trade regulations by the East Java Provincial Office of Industry and Trade and law enforcement authorities has not been effective, as enforcement has been limited to socialization efforts without the imposition of strict sanctions. Obstacles to implementation include regulatory constraints, limited authority, insufficient human resources, and low public awareness.